2003
DOI: 10.1207/s15327736me1602_1
|View full text |Cite
|
Sign up to set email alerts
|

Books and Digital Technology: A New Industry Model

Abstract: Adoption theory analysis of the e-publishing industry indicates that consumer acceptance of current technology is the greatest barrier to attaining a critical consumer mass. New electronic paper technologies will soon offer a superior consumer alternative. Publishers will be faced with new opportunities and nagging issues related to new competition, content control, and protection of revenue streams requiring strategies that stress rationalization of distribution systems, cross-promotion, strategic pricing, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The publishing companies are responsible for promotion, by engaging the proper promotional channels. This strategy is very similar to that described by Shaver & Shaver (2003), Earp & Kornis (2005) and Fonseca (2013). The publishing company is one of the main links in this chain, because it determines the book cover price (Svaldi, 2010).…”
Section: Theoretical Framework the Brazilian Publishing Chainsupporting
confidence: 80%
“…The publishing companies are responsible for promotion, by engaging the proper promotional channels. This strategy is very similar to that described by Shaver & Shaver (2003), Earp & Kornis (2005) and Fonseca (2013). The publishing company is one of the main links in this chain, because it determines the book cover price (Svaldi, 2010).…”
Section: Theoretical Framework the Brazilian Publishing Chainsupporting
confidence: 80%
“…Two strategies dominate the landscape: narrowcasting and community-subscriber services (Kist, 2008). Narrowcasting refers to the strategy of discovering discrete markets or user communities who share strong interest in very specific literature, and then offering them targeted products that are based on market analysis (Shaver and Shaver, 2009). This approach is greatly assisted by "viral marketing," a common term in the Internet era, which describes how news of events or products can travel very quickly, even circumnavigating the globe in a matter of hours in some instances.…”
Section: Convergent Strategiesmentioning
confidence: 99%
“…The metaphor of the "supply chain"-which guides how goods or services move forward, from creation to the market-has limited ability to explain how business can operate in a networked and digital environment (Yoffie, 1996). In response, researchers are re-imagining the supply chain as a "web" of relationships, which spreads in many directions, and can create new revenue streams even as established revenue streams fade (Shaver & Shaver, 2009;Yoffie, 1996; Institute for the Future, 1996). The print publishing process is quite linear and so publishers continue to find the supply chain paradigm useful, but at the same time, the web of relationships is a useful means for studying the impact of new media.…”
Section: Collaboration As Revenue Protectionmentioning
confidence: 99%
“…Authors are willing to adopt eBooks and the possibilities of self-publishing when they benefit from increasing revenue shares and audience sizes [10]. However, successful self-publishing requires that authors already enjoy popularity; they would not be found otherwise.…”
Section: B Players Along the Value Chainmentioning
confidence: 99%